2020
DOI: 10.1093/bioinformatics/btaa941
|View full text |Cite
|
Sign up to set email alerts
|

PathExt: a general framework for path-based mining of omics-integrated biological networks

Abstract: Motivation Transcriptomes are routinely used to prioritize genes underlying specific phenotypes. Current approaches largely focus on differentially expressed genes (DEGs), despite the recognition that phenotypes emerge via a network of interactions between genes and proteins, many of which may not be differentially expressed. Furthermore, many practical applications lack sufficient samples or an appropriate control to robustly identify statistically significant DEGs. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…have earlier shown that a similar network approach is capable of identifying condition-specific perturbations that are biologically relevant and thus useful for biomarker discovery ( Sambarey et al., 2017b ; Metri et al., 2017 ; Ravichandran et al., 2021 ). Briefly, our method uses a knowledge-based comprehensive human protein–protein interaction network (hPPiN) previously constructed by us ( Table S2 A), renders it specific to each given condition by integrating gene expression data into it, and sensitively mines most perturbed subnetworks and their most influential epicentric nodes ( Sambaturu et al., 2016 , 2021 ; Ravichandran and Chandra, 2019 ). The network analysis carried out for the discovery datasets for TB 0 (week 0) samples versus TR (month 6) yielded subnetworks of size 2,457 nodes, 4,459 edges for GSE89403 -Thompson, and 2,710 nodes, 4,649 edges for GSE122485 -Sambarey, and shared 1,454 common genes between them ( Table S2 B).…”
Section: Resultsmentioning
confidence: 99%
“…have earlier shown that a similar network approach is capable of identifying condition-specific perturbations that are biologically relevant and thus useful for biomarker discovery ( Sambarey et al., 2017b ; Metri et al., 2017 ; Ravichandran et al., 2021 ). Briefly, our method uses a knowledge-based comprehensive human protein–protein interaction network (hPPiN) previously constructed by us ( Table S2 A), renders it specific to each given condition by integrating gene expression data into it, and sensitively mines most perturbed subnetworks and their most influential epicentric nodes ( Sambaturu et al., 2016 , 2021 ; Ravichandran and Chandra, 2019 ). The network analysis carried out for the discovery datasets for TB 0 (week 0) samples versus TR (month 6) yielded subnetworks of size 2,457 nodes, 4,459 edges for GSE89403 -Thompson, and 2,710 nodes, 4,649 edges for GSE122485 -Sambarey, and shared 1,454 common genes between them ( Table S2 B).…”
Section: Resultsmentioning
confidence: 99%
“…While previous works have exploited protein networks to infer transcriptomic perturbations, they have still relied on significantly differentially expressed genes and interpreted them in the context of the network ( 101 , 102 ). We have previously demonstrated ( 12 ), superiority of PathExt over such integrative approaches that nevertheless rely on significant differential expression.…”
Section: Discussionmentioning
confidence: 99%
“…These approaches nevertheless rely on gene-level differential expression as the lynchpin for the downstream network-assisted analyses. An alternative approach - PathExt - that we have recently shown to be superior to DEG-centric approaches ( 12 ), instead integrates transcriptomic data with curated gene networks and instead of identifying differentially expressed genes, identifies differentially active paths in the integrated network, and then identifies the central genes mediating the differential activities of the most perturbed paths. This alternative approach is based on the recognition that (i) gene expression is noisy and DEGs can therefore lead to false positives, and (ii) key regulatory genes that mediate global transcriptomic changes and thus present a potent target may themselves not be differentially regulated and will thus be missed by DEG-centric approaches.…”
Section: Introductionmentioning
confidence: 99%
“…3. This method of computing response networks which involves a knowledge-based network and a sensitive interrogation algorithm has been shown to outperform data-driven network inference methods in capturing biologically relevant processes and genes (Ravichandran and Chandra, 2019;Sambaturu et al, 2021). Briefly, the network mining algorithm works by computing minimum weight shortest paths, in which each path begins from a source node and ends with a sink node, identifying connected sets of edges that make up the least-cost paths.…”
Section: Reconstruction Of Human Gene Regulatory Network (Hgrn)mentioning
confidence: 99%